Effect ESG on Financial Performance - Muhammad Affan Rizqi; Munari (Owner : Riset dan Jurnal Akuntansi, 2023)
Studies related to this research topic still have inconsistent results. The research objective was to examine and determine the effect of corporate social responsibility, environmental performance and sustainability report disclosure on financial performance. Manufacturing companies have a sizable contribution to environmental pollution, so the researchers decided that manufacturing companies on the Indonesia Stock Exchange for the 2018-2021 period were the population. This research uses quantitative methods and uses secondary data. Purposive sampling was used as a sampling technique in this study. Companies that fulfill the sample are 10 for 4 years (40). Partial least square is used as a data analysis technique. The results of the study show that corporate social responsibility has a significant positive effect on financial performance, while environmental performance and sustainability reports have an insignificant positive effect.